International Interdependencies of Stock Markets: How Influential are Well Established Exchange in Affecting Movements on The KLSE? - Mat Saad Abdullah; Ismail Abdullah (Asian Academy of Management Journal, 2001)
Several analysis assert that linkages among economies primarily, determine the tendency for stock markets to move together across countries. National stock markets from the countries, which have close trade relations, are believed to be highly correlated. If this is the reality, given the openness of the Malaysian economy, how influential are foreign (well-established) equity markets in affecting movements on the Kuala Lumpur Stock Exchange (KLSE)? This paper examines the magnitude and behaviour of co-movements between the KLSE and major stock markets from the developed part of the worls. Using the weekly share price indices from the above-mentioned markets for a period of 1984 through 1994, the data are examined from both perspectives : contemporaneous as well as lead-lag interdependencies. Towards this end, the techniques of correlation and partial correlation analyses are utilized. Findings of the study inter alia, suggest that stock return correlations between the KLSE and well-established stock markets have been significantly positive. However, these return correlations are not stable over time. These markets are found to have the tendency to move very closely together during the periods of turbulence (or down markets). The stock markets from Australia, Hong Kong, Swwitzerland and the United States (U.S) are among these exchanges that are found to be influential in affecting movements on the KLSE. In general, in terms of (contemporaneous) partial correlation, about 10% and 9% of the movements on the KLSE can be explained respecbtively, by the movements on the stock markets of Australia and Hong Kong.